PENGARUH PELATIHAN TERHADAP KINERJA PEGAWAI DI UPTD PUSKESMAS LAHUSA KABUPATEN NIAS SELATAN - Laia, Normal (Jurnal Ilmiah Mahasiswa Nias Selatan, 2025)
The aim of this research is to determine whether there is an influence of training on employee performance at the UPTD Lahusa Community Health Center, South Nias Regency. The type of research used is quantitative research which is associative in nature. The data source is from employees at the UPTD Puskesmas Lahusa, South Nias Regency, with a population of 30 people and the sample in this study was 30 respondents. The data collection technique is by using research instruments or questionnaires. The data analysis method used is simple regression analysis. The results of this research show that the Training variable (X) influences employee performance (Y) with a calculated t value of 6.924 which is greater than the t table value of 1.701. Meanwhile, the simple linear regression equation is Y= 15.910 + 0.619 . %. Thus, it can be concluded that training greatly improves the performance of employees at the Lahusa Community Health Center UPTD, South Nias Regency.